Anomalous course of the left anterior descending coronary artery between the aorta and pulmonary trunk: a rare cause of myocardial ischaemia at rest. Issue 4 (October 1994) - Roynard, J L; Cattan, S; Artigou, J Y; Desoutter, P
Abstract : When the left anterior descending coronary artery follows an anomalous course between the aorta and pulmonary artery it can cause myocardial ischaemia or sudden death during exercise in young people. Coronary arteriography in a 27 year old man with angina pectoris at rest showed a left anterior descending coronary artery arising from a common right trunk and running from the aorta to the pulmonary artery. Follow up after revascularisation was uneventful.